Achieving a Record‐High Yield Rate of 120.9 μgNH3 mgcat.−1 h−1 for N2 Electrochemical Reduction over Ru Single‐Atom Catalysts. Issue 40 (10th August 2018) - Geng, Zhigang; Liu, Yan; Kong, Xiangdong; Li, Pai; Li, Kan; Liu, Zhongyu; Du, Junjie; Shu, Miao; Si, Rui; Zeng, Jie
Abstract: The electrochemical reduction of N2 into NH3 production under ambient conditions represents an attractive prospect for the fixation of N2 . However, this process suffers from low yield rate of NH3 over reported electrocatalysts. In this work, a record‐high activity for N2 electrochemical reduction over Ru single atoms distributed on nitrogen‐doped carbon (Ru SAs/N‐C) is reported. At −0.2 V versus reversible hydrogen electrode, Ru SAs/N‐C achieves a Faradaic efficiency of 29.6% for NH3 production with partial current density of −0.13 mA cm −2 . Notably, the yield rate of Ru SAs/N‐C reaches 120.9 μ g NH 3     mg cat . − 1     h − 1, which is one order of magnitude higher than the highest value ever reported. This work not only develops a superior electrocatalyst for NH3 production, but also provides a guideline for the rational design of highly active and robust single‐atom catalysts. Abstract : Ru single atoms distributed on nitrogen‐doped carbon (Ru SAs/N‐C) exhibit a record‐high activity for N2 electrochemical reduction. At −0.2 V versus reversible hydrogen electrode, Ru SAs/N‐C achieves a Faradaic efficiency of 29.6% for NH3 production with a yield rate of 120.9 μ g NH 3     mg cat . − 1     h − 1, which is one order of magnitude higher than the highest value ever reported.